Radiation risk for patients undergoing cardiac computed tomography examinations. (February 2021) - Alkhorayef, M.; Sulieman, A.; Alzahrani, Khalid; Abuzaid, Mohamed; Alomair, Othman I.; Almuwannis, M.; Alghamdi, Salem; Tamam, Nissren; Bradley, David A.
Abstract: The various technological advancements in computed tomography (CT) have resulted in remarkable growth in the use of CT imaging in clinical practice, not the least of which has been its establishment as the most valuable imaging examination for the assessment of cardiovascular system disorders. The objective of this study was to assess the effective radiation dose and radiation risk for patients during cardiac CT procedures, based on studies from four different hospitals equipped with 128 slice CT equipment. A total of eighty-three patients were investigated in this study with different clinical indications. Effective doses were also calculated using software based on Monte Carlo simulation. The mean patient age (years), weight (kg), and body mass index (BMI (kg/m 2 )) were 49 ± 11, 82 ± 12, and 31 ± 6, respectively. The results of the study revealed that the tube voltage (kVp) and tube current-exposure time product (mAs) ranged between 100 to 140 and 50 to 840 respectively. The overall average patient dose values for the volume CT dose index [(CTDIvol ), in mGy)] and dose length product (DLP) (in mGy·cm) were 34.8 ± 15 (3.7–117.0) and 383.8 ± 354 (46.0–3277.0) respectively. The average effective dose (mSv) was 15.2 ± 8 (1.2–61.8). The radiation dose values showed wide variation between different hospitals and even within the same hospital. The results indicate the need to optimize radiation dose and to establish diagnostic reference levels (DRLs) for patients undergoing coronary computed tomography angiography (CCTA), also to harmonize the imaging protocols to ensure reduced radiation risk. Highlights: Effective radiation dose was assessed for patients during coronary computed tomography angiography (CCTA) procedure. The dose was quantified at four different hospitals equipped with 128 slices CT equipment. The use of effective dose to compare doses with previous studies under estimate the radiation dose. Radiation doses are imaging protocol dependent and varied among different departments. The results indicates the necessity to harmonies the imaging protocols to reduce the preventable radiation risk.